Hubungan kadar ferritin dengan TSH dan FT4 akibat transfusi berulang pada penderita thalassemia di RSUP Dr. Kariadi, Semarang, Indonesia - Ade Delpita; Banundari Rachmawati (DiscoverSys Inc., 2019)
Background: Thalassemia is a genetic disease that results in abnormal formation of globin chains. Patients with thalassemia led to thyroid dysfunction. Levels of Thyroid Stimulating Hormone (TSH) and Free T4 (FT4) were used to determine the function of the thyroid particularly in a repeated transfusions of thalassemia patients. This study aim to analyze the correlation of ferritin with TSH and FT4 levels due to repeated transfusion in thalassemia patients.Methods: Retrospective study of analytic observational design, a cross sectional study of 33 thalassemia patients in Kariadi Hospital Semarang during the period from September to Oktober 2018. Correlation analysis with Spearman test. Ferritin levels, TSH an FT4 were used Elisa method. The data were analysed with the SPSS program using the Spearman correlation test Results: No Correlation analysis between Ferritin levels with TSH levels (r=-0,087; p=0,630)Â and there is weak positive correlation between ferritin levels with FT4 levels (r=0,390; p=0,025)Conclusion: There is no correlation between ferritin levels and TSH levels, but there is correlation between ferritin levels and FT4 levels, but Further research is needed to analyze the factors affecting thyroid dysfunction and required additional screening for other thyroid function.